Modeling the Phase Equilibria of Associating Polymers in Porous Media with Respect to Chromatographic Applications - Wang, Xiu; Limpouchová, Zuzana; Procházka, Karel; Raya, Rahul Kumar; Min, Yonggang (Polymers, 2022)
Associating copolymers self-assemble during their passage through a liquid chromatography (LC) column, and the elution differs from that of common non-associating polymers. This computational study aims at elucidating the mechanism of their unique and intricate chromatographic behavior. We focused on amphiphilic diblock copolymers in selective solvents, performed the Monte Carlo (MC) simulations of their partitioning between a bulk solvent (mobile phase) and a cylindrical pore (stationary phase), and investigated the concentration dependences of the partition coefficient and of other functions describing the phase behavior. The observed abruptly changing concentration dependences of the effective partition coefficient demonstrate the significant impact of the association of copolymers with their partitioning between the two phases. The performed simulations reveal the intricate interplay of the entropy-driven and the enthalpy-driven processes, elucidate at the molecular level how the self-assembly affects the chromatographic behavior, and provide useful hints for the analysis of experimental elution curves of associating polymers.
Keywords: partition coefficient; association; amphiphilic diblock copolymer; size-exclusion chromatography; critical micelle concentration; Monte Carlo simulation; micellar liquid chromatography